Finite Element Analysis of Pushout Test for Stirrup Shear Connector - Lazim, Hussein R.; Jasim, Nabeel Abdulrazzaq (Basrah Journal for Engineering Sciences, 2023)
This numerical study was conducted to simulate and analyze the pushout test for the new shear connector in a new steel-concrete composite system. In this system, the shear stirrups of the reinforced concrete beam are used as shear connectors when passed through holes drilled in the web of inverted steel T-section. The numerical analysis was performed by creating a three-dimensional finite element model using the finite element program ANSYS 21 student version to simulate the behavior of the new innovative shear connectors. The pushout specimens analyzed in this study have been tested experimentally by the same researchers earlier. A total of fifty-six push-out specimens were modeled and analyzed to investigate the effect of many parameters on the shear strength and slip capacity of the shear connector. The parameters studied in this investigation were the specimen dimensions (length and width), the diameter of stirrups (shear connector), the number of connectors per specimen, concrete strength, size of T-section, and shape of the specimen. The finite element analysis using ANSYS gave a good prediction of the effect of studied parameters on connector strength, the failure modes, the form and intensity of deformations in the model, and the load-slip response. The maximum difference in connector strength which was observed between the numerical and experimental results was 15 %.